PROVENANCE OF PRECAMBRIAN FE- AND AL-RICH METAPELITES IN THE YENISEY RIDGE AND KUZNETSK ALATAU, SIBERIA: GEOCHEMICAL SIGNATURES - Likhanov I.I.; Reverdatto V.V. (My University, 2007)
Major, trace and rare earth element contents of Fe- and Al-rich metapelites from the Korda (Yenisey Ridge) and Amar (Kuznetsk Alatau) formations were determined to examine the nature, origin and evolution of their protoliths. Results indicate that these rocks are the redeposited and metamorphosed products of Precambrian kaolinitic weathering crusts, while the geochemical distinctions between the studied metapelites are determined by different weathering conditions in the source area and tectonic settings. The protolith of the Korda Formation metapelites was produced by erosion products of the post-Archean granitoid rocks, which accumulated under humid climate conditions in shallow-water basins along the continental margin. The geochemical characteristics of the deeper primary deposits of the Amar Formation suggest that volcanogenic material of mafic composition derived from an island-arc environment had a major role in supplying the erosion zone. These results agree with lithofacies data and with the geodynamic reconstruction of the evolution of the Yenisey Ridge and Kuznetsk Alatau during the Mesoproterozoic and Neoproterozoic, respectively. It was shown that REEs had limited mobility during contact metamorphism. The coherent mobility of REEs during collisional metamorphism may be attributed both to mineral reactions responsible for modal changes and to local chemical heterogeneity inherited from the initial protolith.
Keywords: GEOCHEMISTRY; KUZNETSK ALATAU; PELITIC SCHISTS; PROTOLITH; RUSSIA; YENISEY RIDGE; Precambrian::Proterozoic::Mesoproterozoic; Докембрий::Протерозой::Мезопротерозойская; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская